2018
DOI: 10.1038/nature25465
|View full text |Cite|
|
Sign up to set email alerts
|

Asparagine bioavailability governs metastasis in a model of breast cancer

Abstract: Using a functional model of breast cancer heterogeneity, we previously showed that clonal sub-populations proficient at generating circulating tumour cells were not all equally capable of forming metastases at secondary sites. A combination of differential expression and focused in vitro and in vivo RNA interference screens revealed candidate drivers of metastasis that discriminated metastatic clones. Among these, asparagine synthetase expression in a patient's primary tumour was most strongly correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
363
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(381 citation statements)
references
References 22 publications
7
363
0
2
Order By: Relevance
“…Recently, the bioavailability of asparagine was reported to govern breast cancer metastasis, and ASNase could reduce breast cancer metastasis (Knott et al , ). From our results above, SLC1A3‐mediated aspartate/glutamate imports could affect ASNase treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the bioavailability of asparagine was reported to govern breast cancer metastasis, and ASNase could reduce breast cancer metastasis (Knott et al , ). From our results above, SLC1A3‐mediated aspartate/glutamate imports could affect ASNase treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Ye et al () have demonstrated the importance of asparagine synthesis via GCN2‐ATF4 axis for tumor cell survival during nutrient deprivation. And it has been demonstrated the essential role of asparagine in promoting cancer cell proliferation and breast cancer metastasis (Krall et al , ; Knott et al , ; Pavlova et al , ). Our study provides another support for the role of asparagine in cancer biology and puts forward the potential usage of ASNase in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have shown that surgical trauma promoted CTCs implantation and growth, and accordingly accelerated tumor metastasis. In the clinic, most women with breast cancer do not die from primary tumor, but instead from the metastasis after resection . Since metastasis after resection is the leading cause of mortality for TNBC, a preventive therapy prior to tumor resection is urgently needed …”
Section: Introductionmentioning
confidence: 99%
“…Intracellular l ‐Asn levels are suggested to regulate amino‐acid uptake in cells, especially of l ‐Ser, l ‐arginine and l ‐His . Besides, l ‐Asn is considered an important regulator of cancer cell amino acid homeostasis, anabolic metabolism and proliferation …”
Section: Introductionmentioning
confidence: 99%